2021
DOI: 10.1021/acsinfecdis.1c00001
|View full text |Cite
|
Sign up to set email alerts
|

Robenidine Analogues Are Potent Antimalarials in Drug-Resistant Plasmodium falciparum

Abstract: Robenidine is a veterinary drug used in the poultry industry to treat coccidiosis caused by parasites in the Eimeria genus. Though this compound and related aminoguanidines have recently been studied in other pathogens, the chemotype has not been systematically explored to optimize antimalarial activity despite the close genetic relationship between Eimeria and Plasmodium (both are members of the Apicomplexa phylum of unicellular, spore-formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Robenzidene, popularly known as “ Robenidine ,” is 1,3-diaminoguanidine-derived N′, 2-bis­(€-4-chlorobenzylidene)­hydrazine-1-carboximidhydrazide hydrochloride and was possibly the first compound developed as a poultry anticoccidial agent in the early 1970s. This was later extended to the whole range of apicomplexan parasites causing the disease coccidiosis in other smaller cattle such as dog, cat, sheep, goat, and so forth. Very recently, Krollenbrock et al have prepared Robenidine analogues having different substituents on the benzaldehyde moiety and tested them as potential antimalarial drugs in vitro as well as in vivo against Plasmodium falciparum, including multidrug-resistant strains . Over the years, modified Robenidine analogues have also been prepared by several groups and screened for anti-inflammatory activities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robenzidene, popularly known as “ Robenidine ,” is 1,3-diaminoguanidine-derived N′, 2-bis­(€-4-chlorobenzylidene)­hydrazine-1-carboximidhydrazide hydrochloride and was possibly the first compound developed as a poultry anticoccidial agent in the early 1970s. This was later extended to the whole range of apicomplexan parasites causing the disease coccidiosis in other smaller cattle such as dog, cat, sheep, goat, and so forth. Very recently, Krollenbrock et al have prepared Robenidine analogues having different substituents on the benzaldehyde moiety and tested them as potential antimalarial drugs in vitro as well as in vivo against Plasmodium falciparum, including multidrug-resistant strains . Over the years, modified Robenidine analogues have also been prepared by several groups and screened for anti-inflammatory activities .…”
Section: Introductionmentioning
confidence: 99%
“… 1 7 Very recently, Krollenbrock et al have prepared Robenidine analogues having different substituents on the benzaldehyde moiety and tested them as potential antimalarial drugs in vitro as well as in vivo against Plasmodium falciparum , including multidrug-resistant strains. 8 Over the years, modified Robenidine analogues have also been prepared by several groups and screened for anti-inflammatory activities. 9 Other areas where such compounds find applications are colorimetric determination of fluoride, 10 chemo sensor for Hg(II) ions, 11 fluorescent detection of Zn(II) ions, 11 and fluorometric determination of microgram level of gallium in biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Robenidine is widely used in the treatment of coccidial infections in poultry and rabbits, and its antimicrobial efficacy was later evaluated when it was found to be more effective against Gram-positive bacteria, S. pseudintermedius and beta-hemolysis streptococcs, and showed good synergistic effects when used in combination with EDTA against Gram-negative bacteria [ 49 ]. In the structure-activity relationship (SAR) investigation of robenidine, it was found that the antibacterial activity of the 4-OH robenidine analog was significantly reduced, and its methylated analog (4-OCH 3 ) had no antibacterial activity, in contrast, whereas the alkyl substituent analog was more effective, with 4-CH 3 and 4-CH(CH 3 ) 2 being more prominent [ 50 , 51 ]. This shows that 4-OCH(CH 3 ) 2 is essential for the antibacterial activity of IBG.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were synthesized according to the modified literature procedure: 42 acetophenones ( 1 ) (1 g, 8.32 mmol, 1 equiv.) and 1,3 diaminoguanidine hydrochloride ( 2 ) (0.52 g, 4.16 mmol, 0.5 equiv.)…”
Section: Methodsmentioning
confidence: 99%